Pembuatan Pupuk Organik Cair dari Limbah Jeroan Ikan Cakalang (Katsuwonus pelamis) - Suartini, Komang; Abram, Paulus H.; Jura, Minarni Rama (Jurnal Akademika Kimia, 2018)
This study aimed to determine the production of liquid organic fertilizer from offal waste of tuna (Katsuwonus pelamis) by bakasang method,and determined content levels of N, P, and K in liquid organic fertilizer. Levels of nitrogen (N), phosforus (P), and potassium (K) were analyzed using the spectrophotometer Spectro Direct. The results showed that at 5 days of fermentation obtained N, P, and K by 2.49%,1.05%, and 0.98%, respectively, while at 10 daysof fermentation obtained amounted to by 3.74%, 3.20%, and 1.03%, respectively. Fertilizer with bakasang method of manufacture can be done on a 10 day fermentation.